2012
DOI: 10.1258/smj.2012.012108
|View full text |Cite
|
Sign up to set email alerts
|

From encephalitis lethargica to cerebral cytoarchitectonics: the polymath talent of Constantin von Economo (1876-1931), pioneer neuroanatomist, neurophysiologist and military aviator

Abstract: Born in Romania of Greek parents and raised in Trieste, Constantin von Economo was educated and influenced by Vienna's medical and scientific tradition. Better known for his description of encephalitis lethargica, a disease bearing his name, he made several contributions to as varied themes as the cytoarchitecture of the cerebral cortex, sleep regulation, evolutionary brain development and, outside medicine, in aviation. While still a student he showed an aptitude for meticulous accuracy and a skill in combini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…As his interest in neuroscience grew, he completed several internships in various countries across Europe. In Paris he attended the neurology services of Pierre Marie, Fulgence Raymond, and Alexis Joffroy; in Germany he interned with Alois Alzheimer and Emil Kraepelin (in Munich), and with Hermann Oppenheim and Theodor Ziehen (in Berlin) 4,[7][8][9][10] . He also attended other neuropsychiatric services in Nancy…”
Section: Baron Constantin Von Economo (1876-1931)mentioning
confidence: 99%
See 1 more Smart Citation
“…As his interest in neuroscience grew, he completed several internships in various countries across Europe. In Paris he attended the neurology services of Pierre Marie, Fulgence Raymond, and Alexis Joffroy; in Germany he interned with Alois Alzheimer and Emil Kraepelin (in Munich), and with Hermann Oppenheim and Theodor Ziehen (in Berlin) 4,[7][8][9][10] . He also attended other neuropsychiatric services in Nancy…”
Section: Baron Constantin Von Economo (1876-1931)mentioning
confidence: 99%
“…He suggested that the coordination and succession of all alimentation movements are performed as a whole in the substantia nigra, with the involvement of cranial nerves ( facial, hypoglossal, vagus, trigeminal) 12 . In 1917, he first published an article in Wiener Klinische Wochenschrift describing cases of a rare disease occurring during 1916-1917, which he defined as lethargic epidemic encephalitis (later known worldwide as von Economo encephalitis) (Figure 1) 4,[7][8][9][10][11][12][13] . Two additional publications neuropathologically and clinically defined this 4,[7][8][9][10]14 .…”
Section: Main Contributions To Neurologymentioning
confidence: 99%
“…He reported that majority of the Encephalitic lethargica cases were the patients aged 15-45 years, third or fourth decades of life [14]. It was defined as a condition primarily involving prolonged somnolence and paralysis (particularly paralysis of the oculomotor nerve resulting ptosis) [3].…”
Section: Encephalitis Lethargica Epidemica (Von Economo Encephalitis)mentioning
confidence: 99%
“…Patients who experienced difficulties maintaining sleep had lesions at the junction of the midbrain and the diencephalon, whereas patients who suffered from insomnia had lesions in the preoptic area. Lastly the patients who displayed narcolepsy had lesions in the lateral and posterior hypothalamus [1]. A neurological basis for narcolepsy and sleep control had been discovered.…”
mentioning
confidence: 99%
“…von Economo described these sleep attacks as "the dissociation of the cerebral and body sleep observed in a series of akinetic cases, patients being in day time mentally wide awake while their bodies were akinetic and drowsy as in sleep." [1] What he was describing here was the phenomenon of cataplexy, a symptom of narcolepsy, characterized by muscle paralysis associated with waking cortical activity.…”
mentioning
confidence: 99%